Dormancy breaking methods in Umbuzeiro seeds (Spondias tuberosa Arr. Cam.) (Anacardiaceae) for seedling production (Research, Society and Development, 2021)
The umbu tree (Spondias tuberosa Arr. Cam.) (Anacardiaceae) is an exclusively Brazilian species and endemic to the Caatinga Biome, being considered a plant of great socioeconomic importance for the local population. This plant has been suffering a lot of human influence through extractivism, causing its population to wear out. The study aimed to test methods used to break seed dormancy as an alternative to overcome umbu seed dormancy. To carry out the work, the seeds were collected after the fruits fell off the plant and dried, the stern of the fruit was separated and the selection of seeds was made. The seeds were taken to the Agrifood Technology Pole of Arapiraca and were subjected to dormancy breaking treatments (Mechanical Scarification, Chemical Scarification and Imbibition). After the treatments, the seeds were placed to germinate in a germination chamber (BOD) on moistened germitest paper with 2.5 times its dry weight, followed for a period of 60 days. The collected data were subjected to statistical analysis in order to obtain information on the efficiency of the methods regarding the variables on germination. It was found that the methods of breaking the dormancy of the umbu seed are effective and that mechanical scarification proved to be more efficient compared to other methods of breaking dormancy.